posted by Anonymous on .
How do you get m=0? from taking the second derivative? does c=1?
Can you check my work on how I get the derivative of R=M^2(c/2-m/3) NEXT R=1/2(CM^2)-1/3(M^3) NEXT dR/dM=CM-M^2. I checked in the back, and that was the answer for the first part of the equation. Isn't the derivative of constant c, zero? I am confused.
You have it correct. yes, the derivative of a constant is zero, but you didn't take that derivative.
if y= ax
If you took the long way, the uv rule..
dy/dx= a dx/dx + x da/dx
but da/dx is zero (derivative of a constant is zero), os